Algerian gas: troubling trends, troubled policies - Aissaoui, A (Oxford Institute for Energy Studies, 2016)
Despite being one of Europe’s largest pipeline natural gas suppliers and the original and still very active supplier of liquefied natural gas (LNG) worldwide, Algeria has received limited serious attention as an exporter of gas in recent years. One reason may be that the country’s key role has somewhat been eclipsed by new developments in both the European gas scene and in the broader global gas arenas. The geo-political aftermath of the 2014 tensions between Russia and Ukraine has turned attention to the European Union’s increasing dependence on Russian gas. In addition, the start-up of substantial new LNG supplies over the next five years has emphasised the probability of global gas surplus and its likely impacts. Since the OIES Gas Programme’s last paper on Algeria in 2011 several developments have taken place which warrant fresh insights on Algeria’s natural gas sector trends and the outlook for its export potential. While the conclusions of the paper are not optimistic, the causal analysis has parallels in many gas resource-rich countries in the Middle East and North Africa region. Sustained government policies of low domestic prices have neither encouraged rationalization of demand nor provided adequate incentives for upstream investment, ultimately resulting in a severe deterioration of national gas balances. In the case of Algeria, this means being increasingly perceived as short of gas for its export commitments.